Stories about Miranda - Thomas, George C. (2004)
It is no exaggeration to say that Yale Kamisar was present at the creation of Miranda v. Arizona. To be sure, the seeds of Miranda had been sown in earlier cases, particularly Escobedo v. Illinois, but Escobedo was a Sixth Amendment right to counsel case. Professor Kamisar first saw the potential for extending the theory of Escob edo to the Fifth Amendment right against compelled self-incrimination. Escob edo theorized that a healthy criminal justice system requires that the accused know their rights and are encouraged to exercise them. The Escobedo Court read history to teach that no system of criminal justice can, or should, survive if it comes to depend for its continued effectiveness on the citizens' abdication through unawareness of their constitutional rights. No system worth preserving should have to fear that if an accused is permitted to consult with a lawyer, he will become aware of, and exercise, these rights. If the exercise of constitutional rights will thwart the effectiveness of a system of law enforcement, then there is something very wrong with that system